You don't need an invoice, do you? An online experiment on collaborative tax evasion - Lilith Burgstaller; Katharina Pfeil (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2022)
Collaborative evasion of taxes and social security fees is prevalent in household services, when a household hires a service provider and no third party is involved. However, evidence on the determinants of collaborative tax evasion in general and the household context in particular is lacking. This paper examines two coordination mechanisms of collaborative tax evasion: A partner's signaled intention and information about majority's evasion behavior (empirical evasion expectation). We implement an interactive tax evasion game in an online labor market (MTurk) with 560 participants. Our findings show that priming with an empirical evasion expectation increases the fraction of evaded transactions by 20 percentage points. Our treatment manipulation of intention signals does not render a significant effect on evasion. However, when willingness to evade is signaled first in the chat, the probability of evasion increases by 45 percentage points.
Keywords: H26; E26; O17; D91; 330; Collaborative Tax Evasion; Compliance; Social Norm; Intention; Online Experiment